PRODUK PENDAFTARAN TANAH SISTIM LENGKAP BERUPA SERTIFIKAT - Samadi, Wibowo Murti; Budiastuti, Shinta Rukmi (ADI WIDYA : JURNAL PENGABDIAN MASYARAKAT, 2021)
We do this Community Service activity with the aim of increasing the understanding of Pulisen residents, especially RT.07 / RW.08 in understanding about obtaining certificates through the PTSL program, this is done incidentally as a State program carried out by BPN The method used in the implementation of this Community Service activity is to use the lecture method, followed by a question and answer (discussion) related to the theme of this activity. Based on observations that we have done some time ago, and also accompanied by the results of interviews that are casual in nature, Pulisen residents, especially RT.07 / RW.08, in understanding about obtaining certificates through the PTSL program this is done incidentally as a State program carried out by BPN, including among others: 1. Low understanding of Prona 2. Low understanding of Ayudication 3. The low level of citizen participation in understanding PTSL